PENYUSUNAN LAPORAN KEUANGAN PADA YAYASAN WAKAF ROYATUL ISLAM - Yuri Febriya Ningsih; Eliyanora Eliyanora; Ferdawati Ferdawati (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2025)
The objective of this research is to prepare the financial statements of Yayasan Wakaf Royatul Islam in accordance with generally accepted accounting standards. The foundation is classified as a non-profit entity whose primary purpose is not to generate profit (non-profit-oriented entity). The preparation of the financial statements is based on the Indonesian Financial Accounting Standards for Private Entities (SAK EP), and for non-profit entities, the presentation guidelines are regulated under the Interpretation of Financial Accounting Standards (ISAK) No. 335. The financial statements consist of the statement of financial position, statement of comprehensive income, statement of changes in net assets, statement of cash flows, and notes to the financial statements. The researcher selected Yayasan Wakaf Royatul Islam as the object of the study. This foundation was chosen because it has not yet prepared its financial statements in accordance with the applicable standards, namely the Private Entity Standards and ISAK No. 335. The research data were obtained through interviews and document reviews. In preparing the financial statements, the researcher used Microsoft Excel as a tool to facilitate transaction recording, enabling the generation of financial statements in accordance with ISAK No. 335, which governs non-profit entities.